Avaliação da cinetica bacteriana na biolixiviação de calcopirita - Viegas, Debora Maria Alves [UNESP] (2016)
Technological development of mining and metallurgical industries has increased in recent decades due to constant search for improving life quality. Mining industries are now facing an issue related to the depletion of reserves since the demand for metals is growing progressively year after year. Therefore, he need of extracting metals from low grade ores and industrial wastes become an important key to this sector. For this purpose, processes that require low investment and low operating costs for metal extraction are preferentially used for being economically feasible compared to conventional processes. Bioleaching is one of the main alternative technologies for extracting metals, such as copper one of the most important metals for over five thousand years, due to its properties and formation of metal alloys. Copper is one of the largest economic interest metals. About 70% of this metal is found in nature as chalcopyrite (CuFeS2). This is the most abundant mineral among all types of copper sulfide ores. Copper bioleaching from chalcopyrite is considered more economically and environmentally sustainable than conventional pyrometallurgical processes. The main microorganisms involved in this process are the well-known Acidithiobacillus ferrooxidans, mesophilic bacteria capable of using ferrous ions and reduced sulfur compounds as energy source through oxidative reactions Leptospirillum ferrooxidans also mesophilic and able to oxidize ferrous ions as energy source. The addition of carbohydrates, proteins and other substances of biological origin has also been a factor tested in assays aiming to improve the performance of the process. In this context, this study aimed to evaluate the ability to solubilize copper from chalcopyrite mediated by both At. ferrooxidans and L. ferrooxidans separately and combined, as a consortium. Besides, to evaluate the efficiency of the process adding cysteine in the growth medium. A previous study of oxidation of ferrous ions in the presence of cysteine was performed to determine the inhibitory concentrations for the growth of the strains. In general, bioleaching tests were performed in shake flasks at 150 rpm, 30 °C, in the presence of 2.5% (w/v) of chalcopyrite in T&K medium, 5% (v/v) inoculum and 10-3 mmol.L-1 of cysteine. Evaluating the influence of the consortia and species isolated in the process, it was determined that the vials containing the At. ferrooxidans - LR adapted showed the highest recovery percentages (23.2%) after 35 days. Abiotic systems showed a negligible recovery of copper, reaching only 6% in an average potential of 350 mV (Ag / AgCl). The addition of cysteine promotes an increase in copper recovery compared to the same condition in the absence of cysteine. Differences were detected in the copper extraction in different conditions inoculated by establishing the following descending order: At. ferrooxidans - LR + cysteine (25.3%) > At. ferrooxidans - LR (23.5%) > mutant + cysteine (23.0%)> L. ferrooxidans + cysteine (20.3%)> mutant (20.0%)> L. ferrooxidans (18.0%). Finally a statistical analysis was performed to determine the correlation between the parameters studied, pH, Eh and [Fe3+]/[Fe2+] and copper solubilization for each microorganism. The results showed a high correlation (>75%) in 85% of cases, where for bacteria At. ferrooxidans the highest correlation was found to the parameter [Fe3+]/[Fe2+] and differently for the bacteria L. ferrooxidans the highest correlation it was related to the solubilization pH.